Neuropsychiatric adverse effects of interferon-α: Recognition and management - RAISON, Charles L; DEMETRASHVILI, Marina; CAPURON, Lucile; MILLER, Andrew H (CNS drugs, 2005)
Recombinant preparations of the cytokine interferon (IFN)-alpha are increasingly used to treat a number of medical conditions, including chronic viral hepatitis and several malignancies. Although frequently effective, IFN alpha induces a variety of neuropsychiatric adverse effects, including an acute confusional state that develops rapidly after initiation of high-dose IFN alpha, a depressive syndrome that develops more slowly over weeks to months of treatment, and manic conditions most often characterised by extreme irritability and agitation, but also occasionally by euphoria. Acute IFN alpha-induced confusional states are typically characterised by disorientation, lethargy, somnolence, psychomotor retardation, difficulties with speaking and writing, parkinsonism and psychotic symptoms. Strategies for managing delirium should be employed, including treatment of contributing medical conditions, use of either typical or atypical antipsychotic agents and avoidance of medications likely to worsen mental status. Significant depressive symptoms occur in 21-58% of patients receiving IFN alpha, with symptoms typically manifesting over the first several months of treatment. The most replicated risk factor for developing depression is the presence of mood and anxiety symptoms prior to treatment. Other potential, but less frequently replicated, risk factors include a past history of major depression, being female and increasing IFN alpha dosage and treatment duration. The available data support two approaches to the pharmacological management of IFN alpha-induced depression: antidepressant pretreatment or symptomatic treatment once IFN alpha has been initiated. Pretreatment might be best reserved for patients already receiving antidepressants or for patients who endorse depression or anxiety symptoms of mild or greater severity prior to therapy. Several recent studies demonstrate that antidepressants effectively treat IFN alpha-induced depression once it has developed, allowing the vast majority of subjects to complete treatment successfully. Recent data suggest that IFN alpha-induced depression may be composed of two overlapping syndromes: a depression-specific syndrome characterised by mood, anxiety and cognitive complaints, and a neurovegetative syndrome characterised by fatigue, anorexia, pain and psychomotor slowing. Depression-specific symptoms are highly responsive to serotonergic antidepressants, whereas neurovegetative symptoms are significantly less responsive to these agents. These symptoms may be more effectively treated by agents that modulate catecholaminergic functioning, such as combined serotonin-noradrenaline (norepinephrine) antidepressants, bupropion, psychostimulants or modafinil. Additional factors to consider in selecting an antidepressant include potential drug-drug interactions and adverse effect profile. Finally, IFN alpha appears capable of inducing manic symptoms. Mania, especially when severe, is a clinical emergency. When this occurs, IFN alpha and antidepressants should be stopped, an emergency psychiatric consultation should be obtained, and treatment with a mood stabilizer should be initiated.